Structure and floristic composition of mangroves in the Bahía de Cispatá, Colombian Caribbean - Agudelo, Claudia Milena; Bolívar, Jhoanata; Polanía, Jaime; Urrego, Ligia E.; Yepes, Adriana; Sierra, Andrés (Revista de Biología Tropical, 2015)
Mangroves are plant associations that are easily adapted to saline conditions and fluctuating levels of flooding. This ecosystem provides a wide variety of goods and services as carbon storage. Structural differences, species composition and micro-environmental characteristics between physiographic types involve differences in carbon storage in their soils. This research aimed to identify the variation of mangrove species through changes in the physical-biotic variables of mangrove forest of Cispatá bay, Colombia. We measured structural variables of forest (D, H, density of individuals) as well as physico-biotic variables (flood level, A. aureum coverage, water interstitial salinity, soil pH, % N, % COs, roots and apparent density soil) in 12 plots established randomly. With a CCA it was identified three mangroves: basin, fringe in good condition and fringe with anthropogenic intervention. The first was dominated by A. germinans and the others by R. mangle. The basin mangrove differs from fringe in physical-biotic variables and structurally, it presented the highest values of COs, salinity, apparent density and pH. Although the two fringe mangrove exhibit similar physical-biotic variables, human disturbance may strongly change the structure of one of them. It was concluded that the distribution of mangrove species of bay responds to a spatial variation in environmental characteristics. However, anthropogenic intervention is a determining variable in the structure of mangroves which affects estimations of the role of different types of mangrove forests as carbon sinks.